Do role overload and negative emotions lead healthcare workers to cyberloafing? - Wulandari, Aprilia; Silvia Kristanti Tri Febriana; Shadiqi, Muhammad Abdan (HUMANITAS published by Universitas Ahmad Dahlan., 2025)
Cyberloafing is a serious problem in the workplace, including in the health sector. Role overload is a significant stressor that contributes to its onset. Referring to the stressor emotion counterproductive work behavior model, this study aimed to determine the effect of role overload on cyberloafing behavior mediated by negative emotions. This research involved 230 health workers (doctors, nurses, and midwives) in Indonesia as participants. Data was collected using the role overload scale, the Job- Related Affective Well-Being Scale, and the cyberloafing scale (minor and serious) and was analyzed through IBM SPSS Statistics 25 PROCESS Macro Hayes v4.1. The results showed that through negative emotions, role overload both directly and indirectly predicts serious cyberloafing. On the other hand, the role overload did not significantly predict minor cyberloafing; rather, it did so indirectly through the mediator's unpleasant emotions. This research implies how the government could create policies to manage excessive workloads by regulating working hours, providing incentives, and ensuring equitable distribution of healthcare facilities. Organizations could regularly evaluate workloads and offer stress management programs. Healthcare workers could adopt effective stress management techniques and seek professional support when necessary while also communicating openly about role overload.